Building Green Behavioral: The Role of Eco Literacy and Financial Literacy in Moderating Household Finances - Masayu Rizky Kurnianingsih; Asri Nur Wahyuni (Jurnal Dinamika Manajemen, 2025)
Eco literacy among housewives has been increasing, supported by the application of green behaviour in household finances. The purpose of this study is to determine the relationship between green behaviour as an independent variable, eco-literacy and financial literacy as moderating variables, and household finances as a dependent variable. The quantitative research sample involved 100 respondents using snowball and purposive sampling techniques among housewives in Semarang City. The results indicate that green behaviour, eco-literacy, and financial literacy have a positive influence, while Moderated Regression Analysis (MRA) shows that eco-literacy and financial literacy significantly weaken the influence of green behaviour on household finances. These findings not only support the hypothesis that increased environmental understanding can help individuals make appropriate financial decisions, but also highlight challenges in its implementation among the public, necessitating more effective educational strategies.